Testing Marginal Productivity Theory - Archibald, G. C. (Review of Economic Studies, 1960)
Journal Article Testing Marginal Productivity Theory Get access G. C. Archibald G. C. Archibald London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 27, Issue 3, June 1960, Pages 210–213, https://doi.org/10.2307/2296084 Published: 01 June 1960